Oxidative stress and psychological functioning among medical students - Rani Srivastava; Jyoti Batra (Industrial Psychiatry Journal, 2014)
Background: Oxidative stress has gained attention recently in behavioral medicine and has been reported to be associated with various psychological disturbances and their prognoses. Objectives: Study aims to evaluate the oxidative stress (malonylaldehyde (MDA) levels) and its relation with psychological factors (dimensions of personality, levels of anxiety, stress, and depression) among medical/paramedical students of 1 st and 3 rd year). Materials and Methods: A total of 150 students; 75 from 1 st year (2010-2011) and75 from 3 rd year (2009-2010); of medical and paramedical background were assessed on level of MDA (oxidative stress) and personality variables, that is, level of anxiety, stress, and depression. These psychological variables were correlated with the level of their oxidative stress. Results: Findings revealed that both groups are influenced by oxidative stress and their psychological variables are also compatible in order to confirm their vulnerabilities to stress. Conclusions: Stress in 3 rd year students was significantly higher and it was noted that it adversely affects the psychological parameters. Hence, special attention on mental health aspect in these students may be given.